Ciliated Foregut Cyst of the Common Hepatic Duct: An Unusual Mimic of a Type II Choledochal Cyst. (October 2016) - Cottreau, Jonathan; Costa, Andreu; Walsh, Mark; Arnason, Thomas
Ciliated foregut cysts typically arise in the liver and pancreas, with rare cases reported to arise in the gallbladder wall. Herein, we describe an unusual case of a patient with a ciliated foregut cyst arising from the wall of the common hepatic duct, which has not been reported previously. As a result of its unique anatomical location, the cyst was mistaken for a type II choledochal cyst on preoperative imaging. The cyst caused intermittent biliary obstruction that resolved following surgical resection.